Do bans on affirmative action hurt minority students? Evidence from the Texas Top 10% Plan - Kalena E. Cortes (W.E. Upjohn Institute for Employment Research, 2010)
In light of the recent bans on affirmative action in higher education, this paper provides new evidence on the effects of alternative admissions policies on the persistence and college completion of minority students. I find that the change from affirmative action to the Top 10% Plan in Texas decreased both retention and graduation rates of lower-ranked minority students. Results show that both fall-to-fall freshmen retention and six-year college graduation of seconddecile minority students decreased, respectively, by 2.4 and 3.3 percentage points. The effect of the change in admissions policy was slightly larger for minority students in the third and lower deciles: fall-to-fall freshmen retention and six-year college graduation decreased, respectively, by 4.9 and 4.2 percentage points. Moreover, I find no evidence in support of the minority 'mismatch' hypothesis. These results suggest that most of the increase in the graduation gap between minorities and non-minorities in Texas, a staggering 90 percent, was driven by the elimination of affirmative action in the 1990s.
Keywords: I21; I23; J15; J25; 330; Affirmative Action; Top 10% Plan; College Quality; Freshmen Retention; College Graduation; Bildungschancen; Bildungsreform; Wirkungsanalyse; Studierende; Minderheit; Bildungsabschluss; Texas